Digital and smart cities - Willis, Katharine S.; Aurigi, Alessandro (Routledge critical introductions to urbanism and the city, 2018)
Digital and Smart Cities presents an overview of how technologies shape our cities. There is a growing awareness in the fields of design and architecture of the need to address the way that technology affects the urban condition. This book aims to give an informative and definitive overview of the topic of digital and smart cities. It explores the topic from a range of different perspectives, both theoretical and historical, and through a range of case studies of digital cities around the world. The approach taken by the authors is to view the city as a socially constructed set of activities, practices and organisations. This enables the discussion to open up a more holistic and citizen- centred understanding of how technology shapes urban change through the way it is imagined, used, implemented and developed in a societal context. By drawing together a range of currently quite disparate discussions, the aim is to enable the reader to take their own critical position within the topic. The book starts out with definitions and sets out the various interpretations and aspects of what constitutes and defines digital cities. The text then investigates and considers the range of factors that shape the characteristics of digital cities and draws together different disciplinary perspectives into a coherent discussion. The consideration of the different dimensions of the digital city is backed up with a series of relevant case studies of global city contexts in order to frame the discussion with real world examples.